Slavery and dependence in ancient Egypt: sources in translation - Rowlandson, Jane; Bagnall, Roger S.; Thompson, Dorothy J. (Cambridge University Press, 2024)
Ancient Egypt offers rich sources of documentary evidence for the study of the experiences of dependent people, particularly enslaved persons, and how they changed over almost four millennia from the Old Kingdom to the early Islamic period. This volume, the work of a team of scholars spanning the full range of disciplines and languages involved, provides nearly three hundred primary sources in translation, arranged both chronologically and thematically, and is aimed principally at students, instructors and general readers. The documents reveal how people became slaves and ceased to be slaves and how they were traded and exchanged in different periods. They also detail the various kinds of work slaves undertook, whether in the household, in agriculture or in mines and quarries. Introductions explain and contextualise the sources, and particularly address the problems of varying terminology in several different languages. The book shows Egypt's place in the world history of slavery.